18.1: Invited Paper: Roll‐to‐Roll Manufacturing of Printed OLEDs. Issue 1 (1st July 2013) - Hast, Jukka; Tuomikoski, Markus; Suhonen, Riikka; Väisänen, Kaisa‐Leena; Välimäki, Marja; Maaninen, Tiina; Apilo, Pälvi; Alastalo, Ari; Maanineny, Arto
Abstract Organic light emitting diodes (OLED) are developing rapidly and provide a huge market potential for signage, lighting and display applications. Cost efficient manufacturing of OLED components on different flexible substrates is under heavy investigation. In this paper focus is on polymer OLEDs and their non‐vacuum solution processing using roll‐to‐roll (R2R) printing techniques. In this paper VTT's R2R manufacturing process capabilities for printed OLED components are presented. Several demonstrator concepts based on printed OLED technology are introduced including; printed OLED elements 1) in a smart package, 2) a 7‐segment display integrated in a ID‐1 card, 3) an electronics voting card with OLED indicator and 4) a 35 cm2 OLED lighting element printed on glass.